KONSILI VATIKAN II SERTA DAMPAKNYA PADA KARYA KONGREGASI MISI PROVINSI INDONESIA - Cascadarman Deo Putra; Antonius Denny Firmanto; Nanik Wijiyati Aluwesia (Bahasa Indonesia, 2023)
The Catholic Church is more than 2000 years old and in that period of time the Church has undergone many changes. Major changes occurred after the Second Vatican Council was convened which spoke of various aspects of the life of the Church. The Second Vatican Council itself was closed in 1962 which means more than 50 years ago. Talking about change in the Church means that we cannot be separated from the agents of change themselves, which in this case are the clergy, both from a particular diocese and from an institute. In this article, we will discuss how the clergy who in the article narrowed down within the scope of the Congregation of Missions responded to the Second Vatican Council in their lives or in their works? Did the results of the Second Vatican Council have any effect on the Congregation of Missions? To answer these questions, the author will first conduct an in-depth study of the texts produced by the Second Vatican Council and try to see how they relate to the works of the priests of the Congregation for Missions. After conducting studies and various researches related to the themes discussed, the authors found that all the works carried out by the Congregation of Missions were not works that just appeared, but works that try to answer the problems that exist around the Church in the light of the Second Vatican Council.